Open urethroplasty versus endoscopic urethrotomy for recurrent urethral stricture in men: the OPEN RCT. - Pickard, Robert (Health Technol Assess, 2020)
BACKGROUND: Men who suffer recurrence of bulbar urethral stricture have to decide between endoscopic urethrotomy and open urethroplasty to manage their urinary symptoms. Evidence of relative clinical effectiveness and cost-effectiveness is lacking. OBJECTIVES: To assess benefit, harms and cost-effectiveness of open urethroplasty compared with endoscopic urethrotomy as treatment for recurrent urethral stricture in men. DESIGN: Parallel-group, open-label, patient-randomised trial of allocated intervention with 6-monthly follow-ups over 24 months. Target sample size was 210 participants providing outcome data. Participants, clinicians and local research staff could not be blinded to allocation. Central trial staff were blinded when needed. SETTING: UK NHS with recruitment from 38 hospital sites. PARTICIPANTS: A total of 222 men requiring operative treatment for recurrence of bulbar urethral stricture who had received at least one previous intervention for stricture. INTERVENTIONS: A centralised randomisation system using random blocks allocated participants 1 : 1 to open urethroplasty (experimental group) or endoscopic urethrotomy (control group). MAIN OUTCOME MEASURES: The primary clinical outcome was control of urinary symptoms. Cost-effectiveness was assessed by cost per quality-adjusted life-year (QALY) gained over 24 months. The main secondary outcome was the need for reintervention for stricture recurrence. RESULTS: The mean difference in the area under the curve of repeated measurement of voiding symptoms scored from 0 (no symptoms) to 24 (severe symptoms) between the two groups was -0.36 [95% confidence interval (CI) -1.78 to 1.02; p = 0.6]. Mean voiding symptom scores improved between baseline and 24 months after randomisation from 13.4 [standard deviation (SD) 4.5] to 6 (SD 5.5) for urethroplasty group and from 13.2 (SD 4.7) to 6.4 (SD 5.3) for urethrotomy. Reintervention was less frequent and occurred earlier in the urethroplasty group (hazard ratio 0.52, 95% CI 0.31 to 0.89; p = 0.02). There were two postoperative complications requiring reinterventions in the group that received urethroplasty and five, including one death from pulmonary embolism, in the group that received urethrotomy. Over 24 months, urethroplasty cost on average more than urethrotomy (cost difference £2148, 95% CI £689 to £3606) and resulted in a similar number of QALYs (QALY difference -0.01, 95% CI -0.17 to 0.14). Therefore, based on current evidence, urethrotomy is considered to be cost-effective. LIMITATIONS: We were able to include only 69 (63%) of the 109 men allocated to urethroplasty and 90 (80%) of the 113 men allocated to urethrotomy in the primary complete-case intention-to-treat analysis. CONCLUSIONS: The similar magnitude of symptom improvement seen for the two procedures over 24 months of follow-up shows that both provide effective symptom control. The lower likelihood of further intervention favours urethroplasty, but this had a higher cost over the 24 months of follow-up and was unlikely to be considered cost-effective. FUTURE WORK: Formulate methods to incorporate short-term disutility data into cost-effectiveness analysis. Survey pathways of care for men with urethral stricture, including the use of enhanced recovery after urethroplasty. Establish a pragmatic follow-up schedule to allow national audit of outcomes following urethral surgery with linkage to NHS Hospital Episode Statistics. TRIAL REGISTRATION: Current Controlled Trials ISRCTN98009168. FUNDING: This project was funded by the NIHR Health Technology Assessment programme and will be published in full in Health Technology Assessment; Vol. 24, No. 61. See the NIHR Journals Library website for further project information.